A Brief Study on the Growth of Feminism in the Indian Scenario during the Colonial and Post-Colonial Period till 1970s - Pori Borah (International Journal of Psychosocial Rehabilitation, 2020)
Traces of the development of feminist ideology can be seen in the Indian context since the time of arrival of the colonial powers of the west in the motherland. For constituting almost half of the population of each society, women deserves equal share in almost all the aspects of the human society.Earlier, women in the societies of India enjoyed relatively inferior position as compared to its male counterpart. Existence of traditional patriarchal norms and customs has legitimized the male domination in the Indian societies. Under the banner of reformist agenda, the seeds of feminism initiallygrew in the colonial land since the nineteenth century. With due course of time, the grip of feminist ideology gradually became stronger than ever which is evidential in the various writings as well as activities performed by the prominent figures of the land.